2010
DOI: 10.1063/1.3422213
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of the ice temperature dependence of water ice photodesorption

Abstract: The ultraviolet (UV) photodissociation of amorphous water ice at different ice temperatures is investigated using Molecular Dynamics (MD) simulations and analytical potentials. Previous MD calculations of UV photodissociation of amorphous and crystalline water ice at 10 K [S. Andersson et al., J. Chem. Phys. 124, 064715 (2006)] revealed -for both types of ice -that H atom, OH, and H 2 O desorption are the most important processes after photoexcitation in the uppermost layers of the ice. Water desorption takes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(141 citation statements)
references
References 74 publications
(169 reference statements)
6
134
1
Order By: Relevance
“…[40][41][42][43] Starting from the normal hexagonal ice (I h ) crystalline ice configuration (containing 8 bilayers (BLs) (16 MLs) with 60 (30) molecules in each ML), the amorphous ice surface was set up at 10, 20, 60, or 90 K using the "fast quenching" method" [46][47][48] Further details can be found in our previous studies. [41][42][43] Since the resulting amorphous ice surface has a more irregular bonding structure than the crystalline ice surface, 41,47 assigning molecules to MLs is not straightforward. 43 In our most recent study 43 a new definition of ML (binning method 2) was tested and shown to be a more realistic way to assign molecules to MLs.…”
Section: B Amorphous Ice Surfacementioning
confidence: 99%
See 4 more Smart Citations
“…[40][41][42][43] Starting from the normal hexagonal ice (I h ) crystalline ice configuration (containing 8 bilayers (BLs) (16 MLs) with 60 (30) molecules in each ML), the amorphous ice surface was set up at 10, 20, 60, or 90 K using the "fast quenching" method" [46][47][48] Further details can be found in our previous studies. [41][42][43] Since the resulting amorphous ice surface has a more irregular bonding structure than the crystalline ice surface, 41,47 assigning molecules to MLs is not straightforward. 43 In our most recent study 43 a new definition of ML (binning method 2) was tested and shown to be a more realistic way to assign molecules to MLs.…”
Section: B Amorphous Ice Surfacementioning
confidence: 99%
“…[41][42][43] Since the resulting amorphous ice surface has a more irregular bonding structure than the crystalline ice surface, 41,47 assigning molecules to MLs is not straightforward. 43 In our most recent study 43 a new definition of ML (binning method 2) was tested and shown to be a more realistic way to assign molecules to MLs. This binning (method 2) is used in this study and it consists of choosing a molecule and finding the first 23 closest molecules in terms of (x, y) coordinates.…”
Section: B Amorphous Ice Surfacementioning
confidence: 99%
See 3 more Smart Citations